EXPERIMENTAL ANALYSIS IN FEEDING BEHAVIOR - López Espinoza, Antonio (Anales de Psicología / Annals of Psychology, 2007)
Current work presents a revision of the methods used for the experimental analysis of feeding behavior in the last century. Additionally, this revision tries to be described from an historical perspective that allows evaluating the scientific contributions in feeding field. In first place one considers the theoretical antecedents later to examine the importance of "food" like the unit of analysis of feeding pattern. Finally, the mechanisms automated developed from this unit of analysis for the study of feeding behavior are described.